What is the impact of snakebite envenoming on domestic animals? A nation-wide community-based study in Nepal and Cameroon. (July 2021) - Bolon, Isabelle; Babo Martins, Sara; Ochoa, Carlos; Alcoba, Gabriel; Herrera, María; Bofia Boyogueno, Henri Magloire; Sharma, Barun Kumar; Subedi, Manish; Shah, Bhupendra; Wanda, Franck; Sharma, Sanjib Kumar; Nkwescheu, Armand Seraphin; et al.
Abstract: Snakebite envenoming is a life-threatening disease in humans and animals and a major public health issue in rural communities of South-East Asia and sub-Saharan Africa. Yet the impact of snakebite on domestic animals has been poorly studied. This study aimed to describe the context, clinical features, treatment, and outcomes of snakebite envenoming in domestic animals in Nepal and Cameroon. Primary data on snakebite in animals were recorded from a community-based nation-wide survey on human and animal snakebite in Nepal and Cameroon ( Snake-byte project). Mobile teams collected data on snakebite in humans and animals in 13, 879 and 10, 798 households in Nepal and Cameroon respectively from December 2018 to June 2019. This study included 405 snakebite cases (73 in Nepal and 332 in Cameroon) in multiple types of animals. An interview with a structured questionnaire collected specific information about the animal victims. Snake bites in animals took place predominantly inside and around the house or farm in Nepal (92%) and Cameroon (71%). Other frequent locations in Cameroon were field or pasture (12%). A large diversity of clinical features was reported in all types of envenomed animals. They showed either a few clinical signs (e.g., local swelling, bleeding) or a combination of multiple clinical signs. Only 9% of animal victims, mainly cattle and buffaloes and less frequently goats, sheep, and dogs, received treatment, predominantly with traditional medicine. The overall mortality of snakebite was 85% in Nepal and 87% in Cameroon. Results from this nationwide study show an important impact of snakebite on animal health in Nepal and Cameroon. There is a need for cost-effective prevention control strategies and affordable snakebite therapies in the veterinary field to save animal lives and farmer livelihood in the poorest countries of the world. The WHO global strategy to prevent and control snakebite envenoming supports a One Health approach, which may help develop integrated solutions to the snakebite problem taking into account human and animal health. Highlights: Analysis of 405 snakebite cases in animals collected through a nationwide community-based survey in Nepal and Cameroon. Snakebite in domestic animals occurred predominantly inside and around the house or farm. Clinical features of envenoming were diverse in all types of animals. Only 9% of animal victims were treated, mainly cattle and buffaloes, predominantly with traditional medicine. The overall mortality of snakebite in animals was 85% in Nepal and 87% in Cameroon.